PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SUKATANI CIKARANG, JAWA BARAT - Fitri Agustina Peronika Pangaribuan; Tarwijo (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the positive and significant influence of Work Environment variables on Employee performance, to determine the positive and significant influence of Work Discipline variables on Employee performance and to determine the positive and significant influence of Work Environment and Work Discipline variables simultaneously on Employee performance at the Sukatani District Office. The sample used was a saturated sample technique totaling 55 employees. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and f test. The results of the research show that: (1) Partially there is a positive and significant influence between the Work Environment on employee performance at the Sukatani District Office, this can be proven from the simple linear regression equation Y = 8.800+0.454 1.674 significantly 0.006 < 0.05. (2) Partially there is a positive and significant influence between Work Discipline on employee performance at the Sukatani District Office, this can be proven from the simple linear regression equation Y = 10.086+0.545 0.000 < 0.05 . (3) Simultaneously there is a positive and significant influence between the Work Environment and Work Discipline on Employees at the Sukatani District Office, this can be proven from the multiple linear regression equation Y = 7.139 + 0.382 X₁ + 0.273 determination of 78.2%, and a value of ????ℎ???????????????????? 40, 957 > ???????????????????????? 3.175 with a significance level of 0.000 < 0.05.